On Hemionitis atreyu, an invalid and unnecessary name, and on the correct name for that species if placed in Hemionitis (Pteridaceae subfam. Cheilanthoideae) - Mosyakin, Sergei L. (Phytotaxa, 2018)
New molecular phylogenetic and taxonomic publications on cheilanthoid and other ferns (Gastony & Rollo 1998, Smith et al. 2006, Schuettpelz & Pryer 2007, Schuettpelz et al. 2007, Zhang et al. 2007, Christenhusz et al. 2011, Eiserhardt et al. 2011, PPG I 2016, etc.) resulted in numerous recent nomenclatural changes and new taxonomic concepts of a rational generic circumscription in ferns in general and cheilanthoids (Pteridaceae subfam. Cheilanthoideae) in particular. These changes affected many taxa, in particular, the well-known species listed in recent literature mainly as Cheilanthes acrostica (Balbis 1801: 98) Todaro (1866: 215) or Allosorus acrosticus (Balb.) Christenhusz (2012: 284).